Pengaruh Loan To Deposit Ratio Dan Tingkat Suku Bunga Kredit Terhadap Return On Asset - Wulandari, Dini; Sipahutar, Mangasa Augustinus (Jurnal Ilmiah Manajemen Kesatuan, 2021)
Bank is a financial institution that serves as a financial intermediary, which means collecting funds from the public and channel them back to the community in the form of loans. This research Using data from published financial statements and published from Indonesian banks in the period 2015-2019. Using data from Quarterly. The analysis technique used in this research is multiple linear regression analysis to determine how much the relationship between one variable to another variable. In addition, the test results can be concluded by the multivariate coefficient that LDR has a positive effect and no significant effect on ROA, while lending rates have a significant negative effect on ROA. Keywords: Return On Assets (ROA), Loan to deposit Ratio (LDR), Credit interest rate level